Anti-cancer effects of Staphylococcal Enterotoxin type B on U266 cells co-cultured with Mesenchymal Stem Cells. (December 2017) - Ejtehadifar, Mostafa; Halabian, Raheleh; Fooladi, Abbas Ali Imani; Ghazavi, Ali; Mosayebi, Ghasem
Abstract: Background: Malignant plasma cells are responsible for Multiple Myeloma (MM). Myeloma Cells (MCs) are located in Bone Marrow (BM) and are in contact with stromal cells. The BM-derived Mesenchymal Stem Cells (BM-MSCs) affect MCs biology through different mechanisms. Currently, Staphylococcal Enterotoxin B (SEB) has been introduced as an anti-tumor agent that is able to kill cancer cells. The present study examined the effects of SEB on MCs and MSCs as an anti-tumor substance. Methods: U266 cells co-cultured on BM-MSCs and treated with SEB and cell viability was analyzed by MTT assay and flow cytometry. The expression levels of IKKb, IL-6, IL-10, and TGF-β genes were evaluated by Real Time-PCR technique in U266 cells and BM-MSCs. Results: Data showed that in the presence of SEB, BM-MSCs support U266 cells proliferation and survival. Moreover, SEB, BM-MSCs and BM-MSCs Conditioned Medium (CM) up-regulated IL-6 and IL-10 expression in U266 cells. Additionally, U266 cells showed increased levels in IKKb expression in presence of SEB or BM-MSCs, while expression of IKKb in U266 cells was down-regulated in coexistence of SEB with BM-MSCs or SEB with CM. Also, TGF-β remained without any changes. Discussion: All in all, SEB can be an appropriate candidate to decrease proliferation and survival rate of cancer cells and it can make noticeable alteration in expression of some genes in U266 cells and BM-MSCs. Further molecular studies are needed to identify the mechanism of action of SEB on U266 cells and BM-MSCs. Highlights: Malignant plasma cells are responsible for Multiple Myeloma (MM). Myeloma Cells (MCs) are located in Bone Marrow (BM) and are in contact with stromal cells. Currently, Staphylococcal Enterotoxin B (SEB) has been introduced as an anti-tumor agent that is able to kill cancer cells. The present study examined the effects of SEB on MCs and MSCs as an anti-tumor substance. U266 cells co-cultured on BM-MSCs and treated with SEB and cell viability was analyzed by MTT assay and flow cytometry. The expression levels of IKKb, IL-6, IL-10, and TGF-β genes were evaluated by Real Time-PCR technique in U266 cells and BM-MSCs. Data showed thatSEB can be an appropriate candidate to decrease proliferation and survival rate of cancer cells and it can make noticeable alteration in expression of some genes in U266 cells and BM-MSCs. Further molecular an in vivo studies are needed to identify the mechanism of action of SEB on U266 cells and BM-MSCs.